Predictive role of neuron-specific enolase and S100-β in early neurological deterioration and unfavorable prognosis in patients with ischemic stroke - Jiang Ruishu; Lai Youlian (Open Medicine)
We aimed to assess whether neuron-specific enolase (NSE) and S100-β levels are associated with early neurological deterioration (END) in patients with acute ischemic stroke (AIS).